Gaining Back What Is Lost: Recovering the Sense of Smell in Mild to Moderate Patients After COVID-19. (9th October 2020) - Iannuzzi, Lucia; Salzo, Anna Eugenia; Angarano, Gioacchino; Palmieri, Vincenzo Ostilio; Portincasa, Piero; Saracino, Annalisa; Gelardi, Matteo; Dibattista, Michele; Quaranta, Nicola
Abstract: The purpose of our cohort study was to quantify olfactory deficits in Coronavirus disease 2019 (COVID-19) patients using Sniffin' Sticks and a pre-post design to evaluate olfactory recovery. Thirty adult patients with laboratory-confirmed mild to moderate forms of COVID-19 underwent a quantitative olfactory test performed with the Sniffin' Sticks test (SST; Burghardt, Wedel, Germany), considering olfactory threshold (T), odor discrimination (D), and odor identification (I). Results were presented as a composite TDI score (range 1–48) that used to define functional anosmia (TDI ≤ 16.5), hyposmia (16.5 < TDI < 30.5), or functionally normal ability to smell (TDI ≥ 30.5). Patients also self-evaluated their olfactory function by rating their ability to smell on a visual analogue scale (Visual Analog Scale rating) and answering a validated Italian questionnaire (Hyposmia Rating Scale). Patients were tested during hospitalization and about 2 months after symptoms onset. During the hospitalization, the overall TDI score indicated that our cohort had impairments in their olfactory ability (10% was diagnosed with anosmia and more than 50% were hyposmic). Almost all patients showed a significant improvement at around 1 month following the first test and for all the parts of the SST except for odor identification. None of the subjects at 1 month was still diagnosed with anosmia. We also quantified the improvement in the TDI score based on initial diagnosis. Anosmic subjects showed a greater improvement than hyposmic and normosmic subjects. In conclusion, within a month time window and 2 months after symptoms' onset, in our cohort of patients we observed a substantial improvement in the olfactory abilities.